ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN WAJIB PAJAK PENGGUNA E-FILING DI KANTOR PELAYANAN PAJAK PRATAMA BATAM SELATAN - Latif; Efriyenti, Dian Efriyenti (SCIENTIA JOURNAL, 2024)
The aim of this research is to analyze how much impact system quality, perceived convenience, security and confidentiality have on taxpayer satisfaction with e-filing users at KPP Pratama South Batam. This data was collected using a questionnaire which was measured using a Likert scale. The population taken in this research were individual taxpayers who reported their taxes using e-filing who were registered at KPP Pratama South Batam, total 61,479 people and the sample from the Slovin formula calculation the sample was obtained in the research This is a total of 398 individual taxpayer respondents. Data were processed using SPSS 25. The results showed that quality had no effect on taxpayer satisfaction using e-filing, perceived ease had a positive effect on taxpayer satisfaction using e-filing, security and confidentiality had an insignificant effect on taxpayer satisfaction using e-filing and together the quality of the system, perceived convenience as well as security and confidentiality have a positive effect on taxpayer satisfaction with e-filing users at KPP Pratama South Batam. The coefficient of determination of 24.6% the remaining 75.4% is influenced by other variables that were not examined in this research.